A Quantitative Study of the Success of On-Campus Alternative Education Programs as Opposed to Off-Campus Alternative Education Programs - Smith, Amanda (Southwest Baptist University, 2019)
Dropout rates could have long lasting implications in this ever growing global economy. The at risk students who dropout fail to receive a proper education, have a difficult time finding work, and can become a drain on our nation’s resources. Although there has been a great deal of research on the different types of alternative programs, there has been little research on which types of alternative programs are more successful. The research sought to determine if location of alternative education programs play an important role in their success. The purpose of this quantitative study is two-fold. First, to determine if there is a difference in graduation rates of on campus programs versus off-campus programs. Second, to determine what elements are found within each location of alternative education programs which may be associated or related to their graduation rates. The National Alternative Education Association (NAEA) created exemplary practices in 2014 to provide standards of quality and program evaluation criteria as a guide for effective alternative education programs. These exemplars were used to create interview questions for directors of the alternative education programs. The study included school districts of Missouri’s region eight, classified by Missouri’s Department of Elementary and Secondary Education. The results were not definitive, but the effect size suggests environment is an important factor and three exemplars exhibited strong statistical associations. The study will assist school districts and educators in making an informed decision about what type of alternative education program to develop based on the needs of their students. Implications for alternative education program development is discussed along with the need for future research with a larger sample size.